Revision arthroplasty with megaprosthesis after Girdlestone procedure for periprosthetic joint infection as an option in massive acetabular and femoral bone defects.: Revision arthoplasty after girdlestone procedure - Piscopo, Antonio; Pola, Enrico; Fusini, Federico; Cipolloni, Valerio; Piscopo, Davide; Colò, Gabriele; Zanchini, Fabio (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: To evaluate the clinical outcomes of patients treated with Girdlestone procedure (GP) or excision arthroplasty (EA) for periprosthetic infection with massive bone defects and undergoing revision arthroplasty.Methods: All patients treated with EA or GP for hip periprosthetic infection between 2014 and 2017 and sustaining revision arthroplasty (RA) were included in the study. Patients with less than 24 months of follow-up or less than 12 months between GP or EA and RA were excluded. Any sign of implant mobilization or periprosthetic fracture was assessed through X-ray. Patients were evaluated with D’aubignè-Postel hip score before RA and at the last follow-up. Mann-Whitney U test was used to assess differences between pre-RA surgery and last follow-up. P value was set as